2017
DOI: 10.1016/j.rmcr.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab reactivates pulmonary granulomatosis

Abstract: Sarcoid like reaction is a well-known entity that occurs as a consequence to several malignancies or their therapies. Immunotherapy has gained a lot of interest in the past few years and has recently gained approval as first line therapy in multiple advanced stage malignancies. Pneumonitis has been described as complication of such therapy. Granulomatous inflammation has been only rarely reported subsequent to immunotherapy. We describe a case of granulomatous inflammation reactivation affecting the lungs in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…Activation of T‐cell immunity might influence not only the tumour but also the infection with Aspergillus. It is interesting to note that a recent case report showed reactivation of pulmonary granulomatosis caused by the other anti‐PD‐1 antibody, pembrolizumab . Considering this previous case and our case, we speculated that immune checkpoint inhibitors can reactivate T‐cell mediated underlying diseases involving infection and granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of T‐cell immunity might influence not only the tumour but also the infection with Aspergillus. It is interesting to note that a recent case report showed reactivation of pulmonary granulomatosis caused by the other anti‐PD‐1 antibody, pembrolizumab . Considering this previous case and our case, we speculated that immune checkpoint inhibitors can reactivate T‐cell mediated underlying diseases involving infection and granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that PD-1 or PD-L1 expression was increased both in sarcoidosis and in the peripheral blood upon PD-1 blockade treatment, which may contribute to the pathogenesis of SLR (15)(16)(17). Although the exact underlying mechanism remains elusive, a line of cell factors such as interleukin-2, interleukin-12, interferon-g, and tumor-necrosis factor-a is thought to be involved in the formation of granulomatous inflammation (14,18,19). To better understand the clinical presentation of this rare irAE, we briefly summarize all the searchable studies reporting sarcoidosis and SLRs related to ICIs therapy published in the English literature up to February 2021.…”
Section: Case Presentationmentioning
confidence: 99%
“…SLRs refer to the atypical response patterns of localized non-caseating granulomatous inflammation without fulfilling the systemic sarcoidosis criteria. Unlike the typical sarcoidosis which is obscure in etiology, SLR is majorly described in the setting of active cancer or after the delivery of immunotherapy ( 14 ). It was reported that PD-1 or PD-L1 expression was increased both in sarcoidosis and in the peripheral blood upon PD-1 blockade treatment, which may contribute to the pathogenesis of SLR ( 15 17 ).…”
Section: Overview Of the Clinical Features Of Sarcoidosis And Slrs As...mentioning
confidence: 99%
“…There are also some published case reports documenting granulomatous lesions in patients following use of PD-1/PD-L1. Al-Dliw et al ( 89 ) report on a 65-year-old Caucasian woman with superficial melanoma of the left hip who, 1 year after pembrolizumab treatment, had a biopsy showing chronic granulomatous inflammation in histiocytes. The patient was started on a high-dose of intravenous steroids and showed significant clinical improvement.…”
Section: Granulomatous Venereal Diseasementioning
confidence: 99%